Evaluasi penerapan sistem informasi manajemen rumah sakit di bagian rekam medis - Andi Karisma Nurdiyansyah; Farid Agushybana; Septo Pawelas Arso (Universitas Jenderal Achmad Yani Yogyakarta, 2021)
Background: Hospitals utilize technology with the application of software used to process data, namely the Hospital Management Information System (SIMRS). The implementation of SIMRS by some hospitals in Indonesia is aimed at Service and access, Performance improvement, Efficiency, effectiveness, and professionalism. Objective: To evaluate the implementation of SIMRS in the medical records section of Panti Rini Hospital with PIECES analysis. Methods: This research is a descriptive analytic study. The data collection technique used a questionnaire instrument and interviews with respondents using the PIECES (Performance, Information, Economic, Control, Efficiency, and Service) evaluation method. The research sample consisted of 10 people including 9 medical recorders including unit coordinator and head of medical records and 1 head of IT. Result: The Performance aspect is said to be poor, in the Information aspect, system Control, economy, and Service are said to be good, which is 100% for each assessment item.Conclusion: Overall from the system assessment, it can be categorized as good, the resulting Information can be considered by the management for decision making. With the system as well, work becomes more efficient and effective in the use of resources and in Service to patients and management.